Relationship of Habits Eat Fast Food and Macro Nutrition Substance with Nutritional Status of The Students of Makassar 16 Junior High School - Siti Hardianti Ardin; Thresia Dewi Kartini; Retno Sri Lestari (Media Gizi Pangan, 2018)
Lifestyle influencesform of behavior or habits a person in responding to physical and psychological, environmental, social, cultural and economic endurance. One of them is a change in people's behavior in eating patterns in the lives of teenagers now results in changes in nutritional status because they tend to consume unbalanced foods and increase the number of  nutritional risks. Factor for teenagers who want to eat fast food often, which is available in some parts of the school. As a result of Behavioral Changes, some teenagers experience changes nutritional status that needed attention. The purpose of this study is to determine the relationship between fast food eating habits and macro nutrient intake with nutritional status of the students of Makassar 16 Junior High School. The study use a cross sectional study design with an analytical approach. This study uses statistical analysis, the chi-square test of the number of samples as much as 89. The habit of eating fast food is obtained from the food frequency questionnaire by adding the score of each food ingredient then compared with the average score of the total score of all subjects. Intake of macro nutrients is obtained from 2x24 hour form recall. Nutritional status is obtained by weighing and body weight then calculated using BMI. The data is presented in the form of graphs and narratives. The results showed that fast food eating habits tended several times (50.6%), and macro nutrient intake was generally good (52.8%). Nutritional status according to normal BMI was 47 people (52.8%) who had thin nutritional status of 32 people (36%), and those who had fat nutritional status were 10 people (11.2%). There is no relationship between the habit of eating fast food with nutritional status, and there is a relationship between macro nutrient intake and nutritional status values.